Everyone is a Teacher Here Method towards Student Learning Outcomes on Kingdom Animalia Topic - Sati Haryati (Jurnal Report of Biological Education, 2020)
This study aims to improve learning outcomes of students' cognitive abilities in the kingdom animalia concept. The subjects of this study were students of SMAN 1 Surade in class X-5 and X-3 with a total of 41 and 36 people. The research method used in this study is Quasi Experimental Design with Pretest-Posttest control group design research design. The instrument used was question of cognitive ability in the form of multiple choice as the main data source and a questionnaire as supporting data. The cognitive abilities netted from the instruments are C1 (knowing), C2 (interpreting), C3 (sorting) and C4 (interpreting). The results of the study show that the cognitive abilities of students after following Learning Everyone is a Teacher Here has increased from the average value of grades the initial test 62.19 increased to 78.79. Based on testing the hypothesis at the final test, the calculated t value of 262.9 is greater than the t table value of 244. This shows that the learning outcomes achieved there were no significant differences. Students respond towards Learning Everyone is a teacher here on each statement interpreted pretty well on average.